Spatio-temporal variations of nutrients and degree of eutrophication in the waters of the Gulf of Ana María and Guacanayabo, Cuba - Betanzos-Vega, Abel; Garcés-Rodríguez, Yuliesky; Delgado-Miranda, Gilma; Pis-Ramírez, María Aurora (Revista Ciencias Marinas y Costeras, 2012)
Nutrient concentrations and other oceanographic variables were compared (ANOVA) between the Gulfs of Ana María and Guacanayabo in the Southeastern region of Cuba based on nine samples taken during the rainy months in 2009. In addition, the degree of eutrophication was estimated, and horizontal distribution charts were prepared for the eutrophication index of total inorganic nitrogen and phosphorus. The variations of the mean concentration of nutrients were analyzed for three different periods (1972-1973, 1988-91, and 2009). There were significant differences (P < 0.05) in salinity, inorganic phosphorus and silicate between the two gulfs. The spatial distribution of the eutrophication index of total inorganic nitrogen and phosphorus showed gradients that decreased as distance to the coast increased. The Gulf of Guacanayabo showed greater distribution and extension of mestrophic values, less haline characteristics, and higher eutrophication index of total inorganic nitrogen (3.05) than the Gulf of Ana María (2.99). The inorganic phosphorus also showed a higher mean rate in relation with the Ana María Gulf (2.57). In the analysis by periods for both gulfs, the mean concentrations of nitrogen oxides (NOx) decreased in 2009 compared to the 1988-1991 period, the inorganic phosphorus showed an increasing trend, while silicate showed a stepwise decrease from 1972-1973.